Sosialisasi Pembuatan Composter untuk Limbah Dapur Bagi Para Anthophile - Nadzirah Ikasari Syamsul; S Bahri; Mulyadi -; R Hanafi; S Asmal; F Mardin; M Rusman; I Bakri; N Syamsul; D R Mudiastuti; S Mangenre; A B R Indah; M A Darmawan; N Tahir (Faculty of Engineering UNHAS, 2021)
Garbage has become a very classic problem around us, this will have a bad impact on the environment around us if it is allowed to continue. The organic residue that ends up in the landfill will be piled up with other waste and will decompose without oxygen (anaerobic). Therefore, the socialitation of the process of making fertilizers made from kitchen waste can be done by means of a composter. The waste processing process starts from sorting the garbage around the house, including sorting out kitchen waste, then cleaning it and putting it in a composter. Composter is a method of making compost that is more abundant and easy to do among Anthopiles because the tools for making compost come from used materials that are at home. This composter is made of used drums or cans, filters, and filter pipes or hoses. Compost water that comes out of this composter is used to treat flower fertility. in addition to composting at home, we save the earth and provide nutrients to the soil around our homes. .